Casuarinicola, a new genus of jumping plant lice (Hemiptera: Triozidae) from Casuarina (Casuarinaceae) - Taylor, Gary S.; Austin, Andy D.; Jennings, John T.; Purcell, Matthew F.; Wheeler, Gregory S. (Zootaxa, 2010)
A new genus, Casuarinicola Taylor gen. nov., comprising five new species of jumping plant lice (Hemiptera: Triozidae) from Casuarina s.s. (Casuarinaceae) from Australia and New Caledonia, is described. New species are: C. australis Taylor sp. nov., C. nigrimaculatus Taylor sp. nov., C. mucronalatus Taylor sp. nov., C. novacaledonica Taylor sp. nov. and C. warrigalensis Taylor sp. nov. The genus is characterised by the following combination of characters: antenna short, 1.1–1.5 times width of head, genal processes short, conical, 0.2–0.5 times length of vertex, fore wing with broadly rounded to subangular apex, mottled with dark markings (in females of most species) or clear (in males of most species), male proctiger short, with broad lateral expansions, parameres simple, and female proctiger short, broadly rounded, pointed apically and with a pair of broad, flange-shaped lateral lobes. A key to species is provided, together with notes on host associations and distribution.